The Effect of Work Environment Factors and Work Culture on Employees Work Spirit in the Work Area, Basse Sangtempe Utara District, Luwu Regency - Afriani Lumantik; Muh. Yusuf Q; Andi Nadirah Mahmud (Jurnal Mantik, 2022)
The research conducted by the researcher aims to analyze the influence of the work environment and work culture on morale in the Working Area of Basse Sangtempe Utara District, Luwu Regency. Work Environment (X1), Work Culture (X2) are independent variables while Work Spirit (Y) is the dependent variable. The sample in this study was 76 respondents who were taken from the Working Area of North Basse Sangtempe District, Luwu Regency. The analytical tools used by the researcher in this research are multiple linear regression test, determination test (R 2 ) and multiple linear regression test. The results of data processing obtained are that the work environment variable affects work morale as evidenced by t count = 3.138 > t table = 1.665 or t count > t table with a significant value of 0.000 <0.05. And the work culture variable also affects work morale as evidenced by the value of t count = 2.088 > t table = 1.665 or t count > t table. With a significant value of 0.040 <0.05. It can be concluded that if in a company the work environment and work culture are improved, the morale will be better.